An investigation of new product management and performance measurements : A test in Banking Industry - Fong, Sook Fun (Universiti Malaysia Sarawak (UNIMAS), 2012)
The general objective of this study was to investigate the influence of new product management on performance measurements. Specifically, the purpose of this study was to examine the influence of firm image, brand strength, market sensing capability, product innovativeness, and new product quality on new product performance, relational performance and customer satisfaction in local banks in Malaysia. Five broadly hypothesized relationships were tested. Data were collected from the customers who have been with the bank for more than one year. The empirical findings were limited to other services industry such as hotel industry, airline industry and transportation industry. For this research, data collected through questionnaires and were analyzed by using Statistical Package for Social Sciences (SPSS) Version 17.0 for Microsoft Windows and SmartPLS 2.0. Furthermore, confirmatory factor analysis, convergent validity, discriminant validity and reliability were the test that carried out to assess the measurement model, whereas t-Value test used to assess structural model. This study determines the relationship between new product management and performance measurements. The result showed that firm image, brand strength, product innovativeness, and new product quality was positively related to new product performance, relational performance and customer satisfaction. On the other hand, market sensing capability was not positively related to new product performance, relational performance and customer satisfaction. This study may be useful for executives to understand more about new product management such as firm image, brand strength, market sensing capability, product innovativeness, and new product quality in order for them to have a better strategy to achieve performance measurements such as new product performance, relational performance and customer satisfaction. This paper enhances both scholars' and practitioners' understanding about the influence of new product management on performance measurements.